The effect of curcumin on paraoxonase and arylesterase enzyme activities in scaly carp (Cyprinus carpio L) - Akogul, Selman; Yonar, Serpil Mise (Ege Univ, Fac Fisheries, 2020)
In this study, the effect of curcumin on paraoxonase and arylesterase enzyme activities in scaly carp ( Cyprinus carpio) were examined. For this purpose, curcumin was added into the feed during 21 days with 10, 20 and 40 mg/kg doses. At the end of this period, serum, liver and kidney samples were taken from the fish and changes in paraoxonase and arylesterase enzyme activities were investigated. The serum and liver paraoxonase and arylesterase enzyme activities of the curcumin treated groups showed significant increases compared to the control group. The increase in kidney paraoxonase and arylesterase enzyme activities was statistically insignificant.
Keywords: Arilesteraz; Balik; Curcumin; Cyprinus carpio; Enzim; Paraoksonaz